Passacaglia and Chaconne: Interpretation of Tempo in Theoretical Sources of the 18th Century - Alexei A. Panov; Ivan V. Rosanoff (Современные проблемы музыкознания)
There is a lot of information about the chaconne and passacaglia in ancient documents: treatises, prefaces to music publications, musical dictionaries and reference and encyclopedic publications of general vocabulary of the last quarter of the 17th and 18th centuries. At the same time, this information is very contradictory and is often subjective. Articles devoted to these genres are found in the Encyclopædia Britannica, in the Dictionnaire de l’Académie française, in the Encyclopédie of Denis Diderot and Jean Le Rond d’Alembert, in the Neu eröffnete musikalische Bibliothek, oder Gründliche Nachricht nebst unpartheyischem Urtheil von musikalischen Schriften und Büchern by Lorenz Christoph Mitzler in Nathan Bailey’s An Universal Etymological English Dictionary, which has gone through many editions, in Johann Georg Sulzer’s Allgemeine Theorie der schönen Künste, and even in the first edition of Jacques Ozanam’s Dictionaire Mathematique, etc. Of course, the authors of special musical dictionaries in the 18th century (Sébastien de Brossard, Johann Georg Walter, James Grassino, Jean-Jacques Rousseau, etc.) do not ignore the chaconne and passacaglia. Very valuable, objective materials about the tempo of the performance of chaconnes and passacaglia in the 18th century are contained in the works of ancient European musicians — authors of various kinds of pre-metronomical systems for fixing the tempo of the performance of musical works (Charles Masson, Michel L’Affiillard, Louis-Leon Pajot (Comte D’Onzembray), Raoul-Auger Feuillet, Jacques-Alexandre de la Chapelle, Johann Joachim Quantz, etc.). Keywords: passacaglia, chaconne, interpretation of 18th century music, genres of 18th century instrumental music, pre-metronomical systems for recording the tempo of performance For citation: Panov, A. A., Rosanoff, I. V. (2025). Passacaglia and Chaconne: Interpretation of Tempo in Theoretical Sources of the 18th Century. Contemporary Musicology, 9(1), 11―28. https://doi.org/10.56620/2587-9731-2025-1-011-028